Molecular-Beam Epitaxially Grown MgB2 Thin Films and Superconducting Tunnel Junctions. (17th May 2011) - Laloë, Jean-Baptiste; Kim, Tae Hee; Moodera, Jagadeesh S.
Abstract : Since the discovery of its superconducting properties in 2001, magnesium diboride has generated terrific scientific and engineering research interest around the world. With aT C of 39 K and two superconducting gaps, MgB2 has great promise from the fundamental point of view, as well as immediate applications. Several techniques for thin film deposition and heterojunction formation have been established, each with its own advantages and drawbacks. Here, we will present a brief overview of research based on MgB2 thin films grown by molecular beam epitaxy coevaporation of Mg and B. The films are smooth and highly crystalline, and the technique allows for virtually any heterostructure to be formed, including all-MgB2 tunnel junctions. Such devices have been characterized, with both quasiparticle and Josephson tunneling reported. MgB2 remains a material of great potential for a multitude of further characterization and exploration research projects and applications.